GUARANTEEING ADHERENCE TO HUMAN RIGHTS STANDARDS IN INFRASTRUCTURE PROJECTS: A LEGAL EXAMINATION OF THE NATIONAL STRATEGY FOR BUSINESS AND HUMAN RIGHTS IN INDONESIA'S PUBLIC-PRIVATE PARTNERSHIP LEGAL FRAMEWORK - Sihombing, Putrida (Indonesian Law Journal, 2024)
This study analyses the integration of human rights principles into Indonesia’s Public-Private Partnership (PPP) legal framework, focusing on the implementation of Presidential Regulation No. 60 of 2023. The findings indicate that aligning the regulation Indonesia’s PPP framework with international human rights standards, is significant step towards. Key provisions include mandatory human rights due diligence, and the accountability of both public and private actors in projects. Despite this progress, the study identifies that the existing legal framework, such as Presidential Regulation No. 38 of 2015, remains predominantly focused on economic and technical aspects, with limited attention to social and environmental impacts. This gap underscores the need for further efforts to incorporate comprehensive human rights impact assessments and stakeholder engagement into the PPP framework. By drawing on international best practices, the study recommends strengthening legal and institutional mechanisms to ensure PPP projects contribute to equitable, inclusive, and sustainable development.